The Effects of Knowledge of Earnings Persistence, Financial Statement Format, and Concerns about Quality of Earnings - LOW, Bernardine (Institutional Knowledge at Singapore Management University, 2009)
This paper examines whether financial statement users exhibit greater ability to discriminate between high and low-accrual firms when they have greater knowledge of earnings persistence, greater awareness of concerns about the quality of earnings, and when accruals are presented more clearly in the financial statements. I find that users with greater knowledge of earnings persistence and greater awareness of concerns about the quality of earnings have greater discriminative ability. High-knowledge users are not affected by the presence and placement of an accrual subtotal in the financial statements. Low-knowledge users discriminate the most when the accrual subtotal is juxtaposed with accrual line items in the cash flow statement. Low-knowledge users do not discriminate much when the accrual subtotal is not presented, or when the subtotal is presented but is not juxtaposed with accrual line items within the same statement.